2004
DOI: 10.1111/j.1439-0523.2004.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci underlying milling quality of rice (Oryza sativa) grains

Abstract: Milling quality of rice grains is important to both producers and consumers. In this study, quantitative trait loci (QTLs) controlling brown rice rate (BR), milled rice recovery (MR) and head rice recovery (HR) were analysed by composite interval mapping over 2 years using 98 backcross inbred lines (BILs). A total of 12 QTLs for the three traits were detected, of which five were for BR, four for MR and three for HR. The proportion of phenotypic variation explained by individual QTLs ranged from 7.5 to 19.9%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 13 publications
(20 reference statements)
2
41
0
4
Order By: Relevance
“…Therefore, this QTL is likely to exert a minor effect on the apparent quality of brown rice, or it may act only under low temperature conditions (this QTL would not be effective under high temperature conditions such as those in 2004). Li et al (2003) also reported the presence of a QTL associated with chalkiness of the endosperm on chromosome 3. Due to the lack of common DNA marker shared in their and our studies, it is not possible to determine the allelism of these QTLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this QTL is likely to exert a minor effect on the apparent quality of brown rice, or it may act only under low temperature conditions (this QTL would not be effective under high temperature conditions such as those in 2004). Li et al (2003) also reported the presence of a QTL associated with chalkiness of the endosperm on chromosome 3. Due to the lack of common DNA marker shared in their and our studies, it is not possible to determine the allelism of these QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…This trait is considerably affected by genes and also by the environment, especially high temperature immediately after heading. Li et al (2003) reported the presence of a QTL associated with chalkiness of the endosperm on the short arm of chromosome 6 using an F 2 population derived from the cross Nipponbare (japonica)/Kasalath (indica)//Nipponbare. Xu et al (2000) also reported the presence of a QTL associated with chalkiness of the endosperm and the percentage of occurrence of white-core on the short arm of chromosome 6, using F 2 and F 3 populations and an F 10 recombinant inbred line population from a cross between Zh97 and Ming63, the parents of Shanyou63, the most widely grown indica hybrid rice variety in China.…”
Section: Discussionmentioning
confidence: 99%
“…Grain chalkiness is quantitatively inherited and controlled by effects of polygenes that are greatly modified by environments. Some QTLs associated with chalky grain have been identified (Li et al, 2003;Zhou et al, 2009;Liu et al, 2011;Liu et al, 2012). QTL inheritance was shown to be complex (Shi et al, 2002); therefore, if marker-assisted selection (MAS) strategies are applied for (or against) this trait, it is necessary to identify and mark the major QTL involved in trait determination.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the growth of economies and population throughout the world, there is an increasing demand for high-yield and high-quality rice. The grain quality of rice, including that of milling, appearance, cooking and eating, and nutrition, is determined by multiple physicochemical properties [2], and studies on the involved key genes and relevant regulatory mechanisms will help to illustrate the regulatory networks of rice quality control and benefit for the breeding efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the growth of economies and population throughout the world, there is an increasing demand for high-yield and high-quality rice. The grain quality of rice, including that of milling, appearance, cooking and eating, and nutrition, is determined by multiple physicochemical properties [2], and studies on the involved key genes and relevant regulatory mechanisms will help to illustrate the regulatory networks of rice quality control and benefit for the breeding efforts.Starch, which is composed of amylose and amylopectin, comprises ∼90% of dry endosperm of rice seed.The apparent amylose content (AAC) is recognized as an important determinant of the appearance and texture of grain [3]. Thai jasmine rice (KDML 105), one of the best-quality rice with good cooking and eating qualities, has low amylose content (AC) and medium gel consistency (GC) [4].…”
mentioning
confidence: 99%